1998
DOI: 10.1029/98je00948
|View full text |Cite
|
Sign up to set email alerts
|

Cloud structure and atmospheric composition of Jupiter retrieved from Galileo near‐infrared mapping spectrometer real‐time spectra

Abstract: Abstract. The first four complete spectra recorded by the near infrared mapping spectrometer (NIMS) instrument on the Galileo spacecraft in 1996 have been analyzed. These spectra remain the only ones which have been obtained at maximum resolution over the entire NIMS wavelength range of 0.7 -5.2 gm. The spectra cover the edge of a "warm" spot at location 5øN, 85øW. We have analyzed the spectra first with reflecting layer models and then with full multiple scattering models using the method of correlated-k. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 47 publications
10
69
1
1
Order By: Relevance
“…The best fits therefore suggest a deep volume mixing ratio of 0.76-0.90 ppm. These retrieved global averages are consistent with previous 5-μm studies, including Bjoraker et al (1986) who gives a value of 0.7 ppm from airborne spectroscopic observations, and Irwin et al (1998) who gives a value of 0.77 ppm from Galileo NIMS. However, analyses of Cassini CIRS 7.7-16.6 µm observations have reported higher values: Irwin et al (2004) fit the data using a deep volume mixing ratio that varies between 1.0 and 1.5 ppm, while Fletcher et al (2009) found that values of 1.8-1.9 ppm produced the best fit.…”
Section: Phosphinesupporting
confidence: 77%
See 1 more Smart Citation
“…The best fits therefore suggest a deep volume mixing ratio of 0.76-0.90 ppm. These retrieved global averages are consistent with previous 5-μm studies, including Bjoraker et al (1986) who gives a value of 0.7 ppm from airborne spectroscopic observations, and Irwin et al (1998) who gives a value of 0.77 ppm from Galileo NIMS. However, analyses of Cassini CIRS 7.7-16.6 µm observations have reported higher values: Irwin et al (2004) fit the data using a deep volume mixing ratio that varies between 1.0 and 1.5 ppm, while Fletcher et al (2009) found that values of 1.8-1.9 ppm produced the best fit.…”
Section: Phosphinesupporting
confidence: 77%
“…The presence of several cloud decks made up of particles of different materials and/or sizes can act together to "blur out" the individual spectral features, giving a net effect of a roughly grey cloud. This effect, along with the fact that the study focussed on warmer regions where the clouds are thinner, allowed Irwin et al (1998) to fit the Galileo NIMS 5-μm spectra using a 4-level cloud structure, made up of 0.5 µm tholins, 0.75 µm NH 3 particles, and 0.45 µm and 50 µm NH 4 SH particles.…”
Section: Spectral Featuresmentioning
confidence: 99%
“…The radiative transfer, or forward model used in this study is a development of code previously used to analyse Galileo/NIMS observations of Jupiter (Irwin et al, 1998(Irwin et al, , 2001). The code has been converted to run in wavenumber rather than wavelength space and uses the method of correlated-k (Lacis and Oinas, 1991).…”
Section: Forward Modelsmentioning
confidence: 99%
“…of 6~1 O -~ (Kunde et al, 1982), and that at pressures less than 1 bar, the combined effects of vertical eddymixing, photodissociation and equilibration reactions, cause the abundance of phosphine to decrease with height with a fractional scale height (f.s.h.) of approximately 0.3 (Carlson et al, 1993;Irwin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The Galileo entry probe's Neutral Mass Spectrometer measured the abundances of H, He, C, N, O, Ne, S, Ar, Kr, and Xe in Jupiter's atmosphere, between the 0.88 and 21.7 bar levels (Niemann et al, 1998;Mahaffy et al, 2000;Wong et al, 2004). The abundance of P was measured remotely from the Galileo orbiter's Near Infrared Mapping Spectrometer (Irwin et al, 1998). In Fig.…”
Section: Planetary Abundances (Nikku Madhusudhan)mentioning
confidence: 99%